Pemahaman Membaca Dan Siswa Kesulitan Memahami Soal Cerita Matematika di Sekolah Dasar - Fazrul Prasetya Nur Fahrozy (Jurnal Elementaria Edukasia, 2023)
Reading is an attempt to get information from the content of the reading read, by reading a person will get the meaning he is looking for. The low level of reading comprehension of students is a measure of student success in getting a content or information from the Reading, plus in math story problems, of course there are things that students need to understand in order to understand the reading of the math story problem. The purpose of this study is to determine how far the students understand the reading of the text and its relationship with the problem of mathematical stories. The research method used by using literature literature review as many as 30 articles with the latest issue and indexed, adapaun the article to find out and associate concepts and theories on this subject accompanied by the collection of initial data. The results of the study are various speculations emerged from the results of the initial data tests that have been done by the author, such as students do not rewrite the content of the story, students do not answer questions, and student answers are wrong and it turns out there is a link between reading comprehension with understanding math story problems. So this article discusses the ability of students to be able to understand the reading of math story problems, in order to know the problems that exist in the problem.